Chemical Structure and Biological Properties of Sulfated Fucan from the Sequential Extraction of Subantarctic Lessonia Sp (Phaeophyceae) - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Leal-Rifo, D; Moncada-Basualto, M (Elsevier Ltd, 2018)
This work is related to the structural characterization of the sulfated polysaccharide from Lessonia sp and the study of its antioxidant and antiparasitic properties. Sequential extraction afforded D-mannitol as the only low MW sugar alcohol. Extraction with 2% CaCl2 afforded in 3.0% yield, a sulfated fucan (SF). Its major fraction (48.5% yield), isolated by ion-exchange chromatography corresponds to a linear polymer of α-L-fucopyranosil residues linked 1→3, sulfated at the O–4 and partially at O–2 positions. By alkaline extraction, sodium alginate (10.3% yield) was obtained. The antioxidant capacity of SF by ESR showed high elimination index (IC50, mg/mL) of hydroxyl (0.27), alkoxy (10.05), and peroxyl (82.88) radicals in relation to commercial mannitol. SF showed activity against the epimastigote form of Trypanosoma cruzi parasite (250 μg/mL) and low cytotoxicity in murine cells (367 μg/mL). The elimination capacity of radicals in aqueous medium of SF would allow its potential biomedical application. © 2018 Elsevier Ltd